Highlighting Factors Influencing Financial Innovation - Moosavinia, Nafiseh; Rezaei, Nader; Abdi, Rasool; Pakmaram, Asgar (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The objective of this research is to examine the factors influencing financial innovation in companies operating within the capital market.Methodology: The study employs a structural equation modeling (SEM) approach to test the hypothesized relationships. Data were collected through questionnaires from a sample of 70 experts in the field. Confirmatory factor analysis (CFA) was used to validate the constructs, and the model was assessed for fit and reliability using various indices such as Average Variance Extracted (AVE), Cronbach's alpha, and Composite Reliability (CR).Findings: The results indicate that all proposed paths are significant. Causal conditions are found to have a meaningful relationship with financial innovation through financial development phases, liquidity creation, risk management tools, and other factors. The central phenomenon significantly impacts contextual conditions such as GDP growth, regulatory changes, and organizational creativity. Additionally, intervening conditions (risk coverage, commodity-based financing) and strategies (use of Islamic financial instruments, management capability) also significantly influence contextual conditions. Lastly, contextual conditions have a significant effect on the outcomes, including social trust and financial performance.Conclusion: The study concludes that the identified factors significantly influence financial innovation in the capital market. These findings are consistent with previous research, particularly aligning with the results of Abdullah et al. (2022). The research highlights the importance of understanding the relationships between these factors to foster financial innovation effectively.